A molecular dynamics study on adsorption mechanisms of polar, cationic, and anionic polymers on montmorillonite. Issue 3 (11th January 2023) - Qu, Yuanzhi; Lin, Ling; Gao, Shifeng; Yang, Yukun; Huang, Hongjun; Li, Xin; Ren, Han; Luo, Wenjia
Abstract : Adsorption mechanisms and desorption kinetics of anionic, cationic, and nonionic polymers on montmorillonite clay under different temperature, pressure, and salinity conditions are revealed by molecular dynamics simulations. Abstract : Adsorption of polymers on clay in aqueous solutions has wide applications in environmental, medical, and energy-related areas, but the interactions between polymers and clay under varied conditions are still not fully understood. In this study, we investigated the adsorption mechanisms of four polymers belonging to different categories, namely anionic poly(acrylic acid) (poly-AA), cationic poly(diallyldimethylammonium chloride) (poly-DADMAC), nonionic polyacrylamide (poly-AM), and the copolymer of AA and DADMAC (poly-AADADMAC). By using molecular dynamics simulations, we compared the desorption kinetics of these polymers at different temperatures and found that poly-AA and poly-AM have the weakest and strongest adsorption abilities, respectively. Polymer adsorptions are slightly more stable at higher pressures, and high salinity favors the adsorption of charged polymers. Further analysis suggests that the adsorption of anionic poly-AA is less stable than that of cationic poly-DADMAC because the latter is attracted to the negatively charged surface by direct coulombic forces, and poly-AM is stabilized by van der Waals forces and hydrogen bonds. This study provides insights on how to enhance the adsorption affinity of polymers on a clay surface and may help the design or improvement of polymer/clay nanocomposite materials.